Challenges In Implementing The Electronic Identity Card Policy: An Analysis Of Service Quality At The Population And Civil Registration Office Of Bandung City - Roosnelly Wahyuning Setiotirin; Himsar Silaban; Triyuni Soemartono; Gatot Hery Djatmika; Rachma Fitriati (Coopetition)
Implementing the Electronic Identity Card (e-KTP) policy has been underway for over a decade since its launch in 2011. However, various challenges persist, especially in urban areas such as Bandung City, which highlight deficiencies in the quality of public services. This study seeks to explore and analyze the dynamics and challenges associated with implementing the e-KTP policy in Bandung City by examining relevant policy dimensions and the quality of public services. Employing a qualitative research methodology, the study utilizes data collection techniques, including in-depth interviews, focus group discussions, observations, and literature reviews. The findings reveal that the Population and Civil Registration Office in Bandung City faces several organizational challenges, such as limited human resources, inadequate infrastructure, and insufficient inter-agency coordination. Moreover, there is a lack of uniformity in interpreting the policy at the implementation level. Community outreach and socialization efforts have been largely ineffective, resulting in low levels of public awareness and participation in the management of e-KTP. Regarding operational challenges, key issues include a limited supply of blank forms, malfunctioning recording devices, and the absence of an integrated population service system. This study recommends that the successful implementation of the e-KTP policy in Bandung City is closely tied to significant improvements in public policy and service delivery. Essential measures include enhancing organizational capacity, optimizing policy interpretation, and refining application systems to ensure effective implementation of the e-KTP. Ultimately, these improvements would increase public satisfaction and trust in population administration services